The Contribution Of Electronic Accounting To The Accuracy Of Accounting Information And Its Impact On The Financial Performance Of The Organization – A Case Study Of Onciel Corporation - Lamouri Salma; Bennoui Mustafa (جامعة الوادي University Of Eloued, 2024)
This research paper aims to study the role and contribution of electronic accounting in enhancing the reliability of accounting information and its effect on the financial performance of the organization. The theoretical approach utilized descriptive methodology, discussing the concept of electronic accounting, electronic accounting information systems, the key advantages and disadvantages of electronic accounting, as well as the concept of financial performance. A case study of the National Salt Corporation (Onciel) was conducted to explore how accounting software is employed in the processes of inputting and processing accounting data to obtain accurate and reliable accounting information in the form of financial statements and reports. Such information positively influences the evaluation of the organization's financial performance. The study concluded that electronic accounting contributes to providing accurate and reliable accounting information in the form of error-free financial statements. Additionally, its comprehensibility positively affects the organization's financial performance by enabling analysis, assessment, and informed decision-making regarding the financial performance of the organization.
Keywords: Electronic accounting; accounting information; financial performance; electronic accounting information systems